2017
DOI: 10.1175/jpo-d-17-0106.1
|View full text |Cite
|
Sign up to set email alerts
|

Regional Impacts of the Westerly Winds on Southern Ocean Mode and Intermediate Water Subduction

Abstract: Subduction processes in the Southern Ocean transfer oxygen, heat, and anthropogenic carbon into the ocean interior. The future response of upper-ocean subduction, in the Subantarctic Mode Water (SAMW) and Antarctic Intermediate Water (AAIW) classes, is dependent on the evolution of the combined surface buoyancy forcing and overlying westerly wind stress. Here, the recently observed pattern of a poleward intensification of the westerly winds is divided into its shift and increase components. SAMW and AAIW forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 35 publications
4
42
0
1
Order By: Relevance
“…The formation of the SAMW is driven by the combined effect of air-sea fluxes and Ekman pumping (Holte et al, 2012;McCartney, 1977;Rintoul & England, 2002;Sloyan et al, 2010;Sloyan & Rintoul, 2001), which in turn are closely related to overlying westerly winds (Downes et al, 2011(Downes et al, , 2017.…”
Section: Samw Volume Change Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the SAMW is driven by the combined effect of air-sea fluxes and Ekman pumping (Holte et al, 2012;McCartney, 1977;Rintoul & England, 2002;Sloyan et al, 2010;Sloyan & Rintoul, 2001), which in turn are closely related to overlying westerly winds (Downes et al, 2011(Downes et al, , 2017.…”
Section: Samw Volume Change Mechanismmentioning
confidence: 99%
“…Therefore, defining the SAMW using a single homogenous temperature might neglect the dynamic differences between ocean basins. Moreover, Downes et al (2017) found that the mixed‐layer depth (MLD) in the Indian and Pacific Oceans responds differently to wind stress perturbations across SAMW formation zones. They further suggested that the poleward shift of westerly winds rather than an increase in the wind stress curl dominates the SAMW subduction variability in the South Indian Ocean (SIO).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the effect of future changes in surface westerlies, 30–40 previous studies that we are aware of (and possibly many others that we are unaware of) have applied a broad range of poleward shifts and intensifications, with the poleward shift ranging between 0.5° and 10° latitude and wind intensification factors ranging from 10 to over 300% (e.g., Delworth & Zeng, 2008; Downes et al., 2017; Frankcombe et al., 2013; Hogg et al., 2017; Spence et al., 2014; Waugh et al., 2019). Given the wide range of perturbations that have been applied in past studies, some guidance regarding a reasonable estimate of the past and projected changes in the location and strength of the westerly winds in the SH is needed to better facilitate model intercomparison.…”
Section: Introductionmentioning
confidence: 99%
“…Farneti and Gent (2011) and Waugh (2014) also examined the response of the ideal age tracer in these simulations. More recently, several studies have examined the impact of changes in winds on different ocean properties in the same suite of global eddy‐permitting ocean‐sea ice simulations that include separate abrupt intensification or poleward shift wind stress perturbations, as well as a simulation with a combined increase and shift: Hogg et al (2017) examined the changes in the meridional overturning circulation, Downes et al (2017) changes in subduction rates, and Waugh et al (2019) examined changes in the barotropic stream function (BSF) and ideal age. While the above studies have in combination documented how different ocean properties respond to an increase or shift in the surface winds, they have focused almost exclusively on the steady‐state response, and little attention has been paid to time scales for these responses.…”
Section: Introductionmentioning
confidence: 99%